PENGEMBANGAN BUKU BAHAN AJAR KEBERAGAMAN AGAMA UNTUK MENINGKATKAN SIKAP TOLERANSI PADA PEMBELAJARAN SISWA KELAS II SD - Rianawati; Dr. Titin Sunaryati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The unavailability of textbooks on religious diversity is one of the reasons whystudents find it difficult to understand the essence and concepts given by theirteachers at school. The aim of the R & D research is to produce textbooks that aresuitable and have high qualifications which can later be used by teachers andstudents at Insan Taqwa Islamic Elementary School. Research applies the ADDIEmodel which consists of analysis, design, development, implementation andevaluation, and data collection methods using questionnaires. The results of thelanguage expert's assessment obtained a score of 98%, the media expert'sassessment obtained a score of 97%. The effectiveness test before and afterusing the religious diversity teaching material book through the N-Gain calculationproduced a score of 0.78, then the results of the religious diversity textbook fromseveral experts were obtained, namely has excellent qualifications and is verysuitable for use.